DINAMIKA MUSIM PENANGKAPAN IKAN CAKALANG DAN TONGKOL DI PERAIRAN PALABUHANRATU - Nurani, Tri Wiji; Prihatin Ika Wahyuningrum; Muhammad Iqbal; Nurani Khoerunnisa; Gilar Budi Pratama; Elvanri Anggi Widianti (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2021)
The monthly fluctuation of fish catch is closely related to the presence of fish or the fishing season. Information about the fishing season is important to improve the efficiency and effectiveness of fishing carried out by fishermen. Skipjack and longtail tuna are important catches landed by fishermen in Palabuhanratu fishing port, with fishing grounds in the waters around Palabuhanratu. This study aims to describe the dynamics of the catch and the effort to catch skipjack tuna and longtail tuna that land their fish in the Palabuhanratu fishing port and determine the fishing season. The data used is the Palabuhanratu fishing port fisheries statistical data for the 2015-2019 period. Data analysis used catch per unit effort (CPUE) analysis and moving average method. The results showed that the CPUE value of skipjack tuna fluctuates tends to increase by 0,009 tons per trip in 2016 and reaches the highest in 2017 which is around 3,068 tons per trip. The CPUE value of longtail tuna tends to increase from 0,021 tons per trip in 2015 to 0,266 tons per trip in 2019. The skipjack tuna fishing season in Palabuhanratu Waters occurs in March, July to November, while the longtail tuna fishing season occurs from July to November. Keywords: Longtail tuna, fishing season index, moving average model, Palabuhanratu, skipjack tuna